Measurement of the multiplicity dependence of γ production ratios in pp collisions at √sNN=13 TeV - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
The Υ(2S) and Υ(3S) production cross-sections are measured relative to that of the Υ(1S) meson, as a function of charged-particle multiplicity in proton-proton collisions at a centre-of-mass energy of 13 TeV. The measurement uses data collected by the LHCb experiment in 2018 corresponding to an integrated luminosity of 2 fb−1. Both the Υ(2S)-to-Υ(1S) and Υ(3S)-to-Υ(1S) cross-section ratios are found to decrease significantly as a function of event multiplicity, with the Υ(3S)-to-Υ(1S) ratio showing a steeper decline towards high multiplicity. This hierarchy is qualitatively consistent with the comover model predictions, indicating that final-state interactions play an important role in bottomonia production in high-multiplicity events.
Veröffentlicht: 2. Mai 2025
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C.E. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F. Glaser, P.A. Günther, X. Han, S. Hausmann-Menzemer, P. Herrero Gascon, J. Hu, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, M. Schmelling, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, M. Zavertyaev, Y. Zhao, A. Zhelezov und 1129 weitere Personen
Gesehen am 02.03.2026
Im Titel steht der Ausdruck sNN unter dem Wurzelsymbol, NN ist dabei tiefgestellt